Tracer study of Bachelor in Entrepreneurship Program: The case of Universiti Utara Malaysia - Abdullah, Syahrina; Mohamad, Armanurah; Bakar, Habshah; Hashim, Norashidah; Ooi, Yeng Keat (Contemporary Research Center (CRC), Australia, 2013)
Entrepreneurship education in universities is vital in inculcating the entrepreneurial culture and to motivate the graduates to be involved in entrepreneurship and business. In line with the government’s encouragement for entrepreneurship development in Malaysia, Universiti Utara Malaysia (UUM) has introduced the Bachelor in Entrepreneurship with Honours as an academic program during the academic session of 2004/2005. This paper is aimed to identify the effectiveness of the entrepreneurship program as offered by UUM. A number of 61 respondents took part in the research by answering the questionnaire distributed during the 23rd UUM Convocation in the year 2010. The descriptive analysis shows that the program has achieved its goals and the majority of graduates were employed upon graduation. In addition, there are students who set up business as their chosen career.The paper proposes steps and recommendations to the university and the government to improve and enhance the existing curriculum to ensure its relevance in helping to create entrepreneurs.